Reporting verbs in abnormal Quranic readings in the book: Al Muhtasib fi Bayn ibn Jinni (d. 392 h) - Shahla Abdulrazzak Nader; Gulizar Kakil Aziz (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
This study, tagged with (Informative verbs in abnormal Quranic readings in the book of Al-Muhtaseb in explaining the faces of irregular readings and clarifying them by Ibn Jinni (d. With the data of pragmatic linguistics, and specifically with the concept of verbal acts, to reach at the end of its dialogue that the linguistic structure (speech) that includes the descriptive and informative forces that correspond to the external reality to describe events, situations and rigid things as well as the conclusion drawn from verbal events, the research concluded that the informative verbs in Abnormal readings in the book of al-Muhtaseb did not go in one direction, but varied between news about God Almighty and His books revealed to His messengers, including the Holy Qur’an, the Torah, and the Gospel, as well as about the prophets and messengers, and about all people, believers, hypocrites, and infidels. and affective action as described in the theory of speech acts. Which was considered by the modern linguist (Austin) and supported by his students who were apprenticed to his lectures and his modern linguistic studies. The study in its entirety consists of two main requirements that include axes and sub-topics, its first requirement is titled B with news actions about God Almighty and the heavenly books in the book of Al-Muhtaseb by Ibn Jannat (392 AH). As for her second request, it bears the title of news about the prophets, messengers, and people in the book of al-Muhtaseb by Ibn Jinni (d. 392 AH). The study ends its investigation and endeavor with a conclusion in which it deposited its conclusions and a glossary of the sources and references relied upon in its writing.